2019
DOI: 10.3390/ijerph16081369
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Aftershock of a Disaster: A Study of Health Service Utilization and Mental Health Symptoms in Post-Earthquake Nepal

Abstract: Background: In 2015, a 7.8 magnitude earthquake struck Nepal, causing unprecedented damage and loss in the mountain and hill regions of central Nepal. The aim of this study was to investigate the association between healthcare access and utilization, and post-disaster mental health symptoms. Methods: A cross-sectional study conducted with 750 disaster-affected individuals in six districts in central Nepal 15 months post-earthquake. Anxiety and depression were measured through the Depression, Anxiety and Stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The most common research method was the quantitative approach, which included 10 quantitative descriptive studies and four quantitative non-randomised studies. All the studies were conducted in lower-middle-income countries: Nepal (n = 6) [ 27 , 28 , 29 , 30 , 31 , 32 ], Pakistan (n = 4) [ 33 , 34 , 35 , 36 ], India (n = 2) [ 37 , 38 ], Indonesia (n = 2) [ 39 , 40 ], Sri Lanka (n = 1) [ 41 ], and Bangladesh (n = 1) [ 42 ]. Among these, Nepal and Bangladesh have recently risen up from low-income country status to lower-middle-income countries.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common research method was the quantitative approach, which included 10 quantitative descriptive studies and four quantitative non-randomised studies. All the studies were conducted in lower-middle-income countries: Nepal (n = 6) [ 27 , 28 , 29 , 30 , 31 , 32 ], Pakistan (n = 4) [ 33 , 34 , 35 , 36 ], India (n = 2) [ 37 , 38 ], Indonesia (n = 2) [ 39 , 40 ], Sri Lanka (n = 1) [ 41 ], and Bangladesh (n = 1) [ 42 ]. Among these, Nepal and Bangladesh have recently risen up from low-income country status to lower-middle-income countries.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
“…The majority of the studies (14/16) included disaster-affected men and women as the study participants and the other two reported women in particular. One study did not report the age range, although the study included adult community members [ 31 ]. Most of the studies (n = 8) were published between 2018 and 2019, one in 2020, and seven between 2010 and 2012.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Developing countries have started integrating mental health and psychosocial support in their disaster preparedness and response (15)(16)(17). However, recent studies showed that mental health problems especially PTSD, depression, and anxiety were still relatively high in these countries (18,19). Adolescents are vulnerable to their surroundings and may not have adequate knowledge of how to cope with mental health issues and what to do in response to natural disasters.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, one study evaluated MHPSS responses and their long-term implications [8], while another focused on the coordination of activities, the leadership of MHPSS programs, as well as service delivery [15]. Some studies have attempted to answer issues concerning service utilization and mental health outcome [16], social cures for post-traumatic stress [17], and religious interventions [18]. Another recent study explored the mental health impact from earthquakes and resilience amongst earthquake-affected villages, stating that 46% of survivors exhibited moderate to high resilience [19].…”
Section: Introductionmentioning
confidence: 99%